Proposition D’un Instrument De Mesure De La Qualité De Service Perçue Par Les Usagers Des Administrations Publiques Marocaines - Ellamrani Ben Hanana; Souad Houfaidi (European Scientific Journal, ESJ, 2016)
The objective of this article is to describe the development of a measurement scale to assess user perceptions in Moroccan public administrations about the quality of service. The measures were built from a survey of 302 users in the Casablanca-Settat region. The methodology is based on the steps recommended by the paradigm of Churchill (1979). Our contribution focuses on the exploratory phase of development of the ladder allowing the emergence of a factor structure of the theoretical variable quality. After presenting the conceptualization of this construct, the article describes the procedures used to construct a multi-item measure of this concept scale. He then states, from analysis of empirical data, the scale of properties in terms of factor structure and reliability. The results thus show a factorial structure of the quality of service perceived by the users of four components with a total variance explained 69.53%. Only the first component: Justice and equal treatment restores 43% of the total variance. The analysis of the reliability of the scales of the principal components shows that the items of each scale are correlated and coherent with each other with reliability indices varying between 0,77 and 0,89. It is the same for the reliability of the total scale of which Cronbach's alpha was 0,9.